Low temperature synthesis by spray pyrolysis of La0.9Sr0.1Co0.2Fe0.8O3 thin films using ethanol and water as a solvent and their microstructural characterization. Issue 10 (December 2015) - Silva, P.L.B.; Vieira, R.P.; Halmenschlager, C.M.; Oliveira, F.F.; Bergmann, C.P.
Abstract: The synthesis via spray pyrolysis was investigated of lanthanum ferrite films doped with strontium and cobalt (LSCF) on silicon substrates for application as cathodes in solid oxide fuel cells (SOFCs). The following precursors were utilized: La(NO3 )3 ·6H2 O, SrCl2 ·6H2 O, CO(NO3 )2 ·6H2 O, and Fe(NO3 )3 ·9H2 O, with La:Sr:Co:Fe (9:1:2:8) stoichiometry. A solution of water and ethanol (1:3 proportion) was used. The relation among the morphology of the films, i) the temperature of the substrate and ii) the distance of deposition was investigated. The results indicate that it is possible to obtain the LSCF film with a porous morphology at 200 °C and at a distance of deposition of 120 mm. This morphology is adequate for applications of LSCF as a cathode for use in solid oxide fuel cells.